A high-throughput salt lake lithium extraction composite membrane and preparation method thereof

By constructing a three-dimensional gel structure in the interfacial polymerization reaction and using CO2 pore channels, the water flux of the lithium-charge positive charge nanofiltration membrane of the salt lake was improved, and the problem of low water production in the existing membrane was solved, and efficient lithium extraction under high magnesium-lithium ratio was achieved.

CN115888418BActive Publication Date: 2025-04-08BLUESTAR (HANGZHOU) MEMBRANE IND CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211552146.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-04-08
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

Existing positive charge nanofiltration membranes such as PEI nanofiltration membranes have low water yields during lithium extraction in salt lakes, making it difficult to apply to the lithium extraction process of salt lakes with high magnesium-lithium ratio.

Method used

The water flux of the nanofiltration membrane is increased by using a three-dimensional gel as a soft template in the interfacial polymerization reaction and using the gel structure formed by anionic surfactant and n-butanol in the aqueous and oil phases. At the same time, the carbonate decomposes during the reaction to produce CO2, forming small pore channels, further increasing the water flux.

Benefits of technology

The water flux of the lithium-charge positive charge nanofiltration membrane of the salt lake has been significantly improved, and the problem of low water production in the existing membrane is solved, and it can be effectively applied to the salt lake lithium extraction process with high magnesium-lithium ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003981696170000101
    Figure BDA0003981696170000101
Patent Text Reader

Abstract

The present invention relates to a preparation method of a lithium-extracting positively charged membrane in a salt lake, comprising: S1, preparing an aqueous solution and an oily solution respectively: the aqueous solution contains polyethyleneimine, anionic and cationic surfactants and carbonate, and the temperature of the aqueous solution is 65-85°C; the oily solution contains polyacyl chloride monomers and n-butanol, and the temperature is 75-95°C; S2, the surface of the base film is dip-coated with an aqueous solution or the aqueous solution is applied to the base film, the aqueous solution is allowed to stand to be adsorbed on the base film, the residual aqueous solution on the surface of the base film is removed, and the dry film is obtained by drying in the shade or drying; the oily solution is then applied to the dry film, and after standing, the residual oily solution on the surface of the film is removed, and the film is transferred to an oven for heat treatment to obtain a high-throughput lithium-extracting positively charged nanofiltration membrane in a salt lake. The present invention utilizes anionic and cationic surfactants and n-butanol to coexist to form a three-dimensional gel network, uses the gelation as a soft template for interfacial polymerization, increases the hydrophobicity of the functional separation layer, and improves the water production of the PEI positively charged nanofiltration membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium extraction from salt lakes, and in particular to a positively charged membrane for lithium extraction from salt lakes and a preparation method thereof. Background Art

[0002] As human demand for lithium energy gradually increases, the world's lithium consumption (measured in Li2CO3) is also increasing year by year. During the period 2010-2017, global lithium consumption increased by about 6% annually, and is expected to reach about 95,000 tons in 2025. The lithium resources that have been mined and utilized in the world mainly come from solid lithium ore and salt lake brine. At present, lithium salt products produced from salt lakes account for more than 80% of the total lithium products in the world. It can be seen that the reserves of lithium resources in salt lakes are very high. However, magnesium and lithium coexist in salt lake water. According to research, Mg in salt lake water is 2+ / Li + The ratio (mass ratio) is as high as 40-1200. Since the chemical properties of magnesium and lithium are very similar, it is very difficult to separate and extract lithium, which has become a technical bottleneck that is difficult to break through, and has long restricted the development of the brine lithium extraction industry. Membrane separation has become a very promising new technology for lithium separation due to its high efficiency, low energy consumption, simple process operation, and no secondary pollution. The membrane method can be used to extract lithium from salt lake brine, which can solve the technical problem of magnesium-lithium separation in high magnesium-lithium ratio salt lake brine by reducing the magnesium-lithium ratio in the brine. The nanofiltration membrane with positive charge on the membrane surface can effectively separate Mg 2+ , Li + The most commonly used positively charged nanofiltration membrane is PEI (polyethyleneimine) nanofiltration membrane.

[0003] However, PEI nanofiltration membrane has certain disadvantages in use, namely, low water production. The density of amine groups on the PEI molecular chain is relatively high, so that the separation layer on the membrane surface (functional separation layer on the bottom membrane surface) is too dense during interfacial polymerization cross-linking, which seriously reduces the water production of the membrane. In fact, the magnesium and lithium content in most salt lake brines is relatively high, and the osmotic pressure is relatively high. If the membrane has low water production, it cannot be actually used for lithium extraction from such salt lakes with high magnesium-lithium ratios. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for preparing a positively charged membrane for lithium extraction from salt lakes, by constructing a three-dimensional gel near the oil phase side of interfacial polymerization as a soft template for interfacial polymerization, using the decomposed gas in the water phase as a mass transfer channel, and synergistically increasing the water flux of the salt lake lithium extraction membrane, thereby solving the technical problem that the existing positively charged nanofiltration membrane is a PEI nanofiltration membrane with low water production and is difficult to apply to the high magnesium-to-lithium ratio salt lake lithium extraction process.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] In a first aspect, the present invention provides a method for preparing a lithium-extracted positively charged film from a salt lake, comprising:

[0009] S1. Prepare aqueous phase solution and oil phase solution separately

[0010] The aqueous phase solution contains polyethyleneimine, anionic surfactant, cationic surfactant and carbonate, and the prepared aqueous phase solution is maintained at 65-85° C.; the oil phase solution contains polyacyl chloride monomer and n-butanol, and the prepared oil phase solution is maintained at 75-95° C.;

[0011] S2. Interfacial polymerization reaction and heat treatment

[0012] The surface of the base membrane is dipped in an aqueous solution or the aqueous solution is coated on the base membrane, and the aqueous solution is allowed to stand to allow the aqueous solution to adsorb on the base membrane, and the residual aqueous solution on the surface of the base membrane is removed, and the membrane is dried in the shade or blown to obtain a dry membrane sheet; then an oily solution is coated on the dry membrane sheet, and after standing, the residual oily solution on the surface of the membrane sheet is removed, and the membrane sheet is transferred to an oven for heat treatment to obtain a high-throughput salt lake lithium extraction positively charged nanofiltration membrane.

[0013] According to a preferred embodiment of the present invention, in S1, the anionic surfactant is sodium laurate (C 11 H 23 COONa), sodium lauryl sulfate, sodium lauryl sulfonate (C 12 H 25 SO3N), sodium lauryl sulfate (C 12 H 25 OSO3Na), sodium dodecylbenzene sulfonate, sodium palmitate, sodium α-olefin sulfonate, sodium N-oleoyl polypeptide, sodium hexadecyl sulfate, sodium hexadecyl sulfonate and sodium camphor sulfonate;

[0014] The cationic surfactant is one or more of hexadecyltrimethylammonium bromide (SL / CTAB), dodecyldimethylbenzylammonium chloride, alkylhydroxyethyldimethylammonium chloride, dodecyltrimethylammonium chloride, hexadecylpyridinium bromide, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride.

[0015] According to a preferred embodiment of the present invention, in S1, in the aqueous phase solution, the mass concentration of the anionic surfactant is 0.01-0.1 wt %; in the aqueous phase solution, the mass concentration of the cationic surfactant is 0.05-0.5 wt %.

[0016] According to a preferred embodiment of the present invention, in S1, the anionic surfactant is sodium laurate, and the cationic surfactant is cetyltrimethylammonium bromide; in the aqueous phase solution, the mass ratio of the anionic and cationic surfactants is 1-5:10.

[0017] According to a preferred embodiment of the present invention, in S1, the weight average molecular weight of PEI in the aqueous solution is 1000-150000, for example, it can be 1000, 8000, 10000, 30000, 50000, 70000, 80000, 100000 or 150000, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The mass concentration of PEI in the aqueous solution is 0.05-3%, for example, it can be 1%, 1.5%, 2%, 2.5% or 3%, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0018] Polyethyleneimine has a strong positive charge in the solution. After the interfacial polymerization of polyethyleneimine with a higher molecular weight, the stronger the positive charge in the solution, the more conducive to the retention of divalent ions, but at the same time, the higher the density of the functional separation layer, the smaller the water flux. Preferably, the weight average molecular weight of PEI is 70000-100000. Of course, when using PEI with a larger weight average molecular weight, relatively more cyclodextrin or carbonate can be added to the aqueous phase solution to take into account the high salt fraction and high water flux of the positively charged nanofiltration membrane.

[0019] According to a preferred embodiment of the present invention, in S1, the carbonate is any one of sodium carbonate, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate, or a combination thereof. The mass concentration of the carbonate in the aqueous solution is 1-3%.

[0020] According to a preferred embodiment of the present invention, in S1, the mass concentration of n-butanol in the oil phase solution is 0.1-1%.

[0021] According to a preferred embodiment of the present invention, in S1, the polyacyl chloride monomer in the oil phase solution is one or more of trimesoyl chloride, isophthaloyl chloride, 3,3',5,5'-biphenyltetracarboxylic acid chloride, terephthaloyl chloride, and adipoyl chloride; the solvent of the oil phase solution is one or more of n-hexane, isoparaffin Isopar G, and isoparaffin Isopar L, and the mass concentration thereof is 0.01-2%. The preferred mass concentration is 0.2-0.3%. Preferably, the polyacyl chloride monomer is trimesoyl chloride (TMC).

[0022] According to a preferred embodiment of the present invention, in S2, the base film is one or more of a polysulfone base film, a polyethersulfone base film, a polyethylene base film, a polyimide base film, a polypropylene base film, a polyacrylonitrile base film, a polyvinylidene fluoride base film, and a polyvinylidene fluoride base film. More preferably, the base film is a polysulfone base film, and the polysulfone base film includes a substrate such as a non-woven fabric as a strength support and a polysulfone membrane covering the surface of the substrate.

[0023] According to a preferred embodiment of the present invention, in S2, the aqueous solution is first coated on the bottom membrane diaphragm, and the excess aqueous solution on the bottom membrane surface is removed after standing for 30-70 seconds, and the diaphragm is blown dry, and then the oil solution is coated, and the excess oil solution on the diaphragm surface is removed after standing for 30-70 seconds, and the diaphragm is allowed to stand in the air for 3-10 seconds (to promote the completion of the reaction, it can be allowed to stand or not according to the situation), and then transferred to a 40-140°C forced air drying oven for treatment for 2-6 minutes to obtain a high-throughput salt lake lithium extraction positively charged nanofiltration membrane.

[0024] Preferably, the heat treatment includes controlling the heating temperature using an oven, a blast drying oven, a heating plate or a water bath, and the heating temperature is 40-140°C. Preferably, the heat treatment temperature and time are controlled according to the selected solvent of the oil phase solution: if the solvent of the oil phase solution is n-hexane (boiling point 69°C), the heat treatment temperature ranges from 40-100°C, and the treatment time is about 2-6min; if it is Isopar G (initial boiling point 163°C), the heat treatment temperature ranges from 60-120°C, and the treatment time is about 2-6min; if it is Isopar L (initial boiling point 185°C), the heat treatment temperature ranges from 80-140°C, and the treatment time is about 2-6min; under the aforementioned heat treatment conditions, the performance of the prepared nanofiltration membrane is better.

[0025] Before the heat treatment, most of the interfacial polymerization reaction has been completed. The heat treatment is used to promote the completion of the cross-linking reaction and enhance the strength of the functional separation layer.

[0026] In a second aspect, the present invention further provides a high water flux salt lake lithium extraction positively charged nanofiltration membrane, which is prepared by the method described in any of the above embodiments.

[0027] (III) Beneficial effects

[0028] The beneficial effects of the present invention are:

[0029] The present invention adds anionic surfactant and cationic surfactant to the aqueous solution at the same time, and adds n-butane to the oil phase solution at the same time. When an interfacial polymerization reaction occurs to generate a positively charged nanofiltration membrane functional separation layer, the anionic and cationic surfactants and n-butane contact to gel the n-butanol. The generated gel is a three-dimensional network structure, which can be used as a soft template during interfacial polymerization and is retained and distributed in the functional separation layer to increase the water production channel. In addition, the gel itself has hydrophilicity, so it can also increase the water flux of the nanofiltration membrane.

[0030] (2) Carbonate is also added to the aqueous solution. The aqueous solution and the oil solution are coated on the bottom membrane sheet in sequence. During the static process, most of the interfacial polymerization reaction has been completed. Since the aqueous solution and the oil solution maintain a certain initial temperature, H + Under the condition of maintaining a certain initial temperature, carbonate decomposes to produce CO2, which escapes in the form of dispersed single molecules or molecular clusters of microbubbles. The small pores generated after the escaped gas provide mass transfer channels for the anionic and cationic surfactants and n-butanol in the water phase and oil phase to form gels; the escaped CO2 gas can maintain the three-dimensional network structure of n-butanol gel. Due to the presence of the three-dimensional network gel, the looseness of the functional separation layer of the nanofiltration membrane is increased, and the water flux is improved. In addition, the channels generated by the escape process of CO2 gas leave uniform pores on the PEI surface, which also helps to increase the water flux.

[0031] (3) During the interfacial polymerization reaction, the CO2 produced by the decomposition of carbonate can react reversibly with the -NH2 on PEI to temporarily protect the amine group, prevent the cross-linking reaction from being too fast and the cross-linking from being too dense, improve the uniformity of the functional separation layer of the nanofiltration membrane, prevent the cross-linking from being too dense, and ensure water flux. DETAILED DESCRIPTION

[0032] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.

[0033] The present invention improves the prior art mainly in two aspects: first, when synthesizing PEI positively charged nanofiltration membrane; a certain proportion of anionic and cationic surfactants are added to the aqueous solution, and a certain amount of n-butanol is added to the oil phase solution. The mixed system of anionic and cationic surfactants is used to achieve the gelation of n-butanol, and the generated gel is used as a soft template during interfacial polymerization, and is retained and distributed in the functional separation layer to increase the water production channel. Second, carbonate is added to the aqueous solution, and the initial temperature of the aqueous solution and the oil phase solution is maintained before heat treatment, so that CO2 gas can be generated more evenly during the interfacial polymerization reaction. The escape of CO2 gas has the following effects: ① small pores provide a mass transfer channel for the anionic and cationic surfactants and n-butanol in the aqueous phase and the oil phase to generate gel; ② the escaped CO2 gas can maintain the three-dimensional network structure of the n-butanol gel and improve the water flux. ③, after the escape of CO2 gas, uniform pores are left on the surface of PEI, increasing the water flux. ④ Reversibly react with -NH2 on PEI to temporarily protect the amine group, prevent the cross-linking reaction from being too fast and the cross-linking from being too dense, and make the structure of the functional separation layer of the nanofiltration membrane more uniform.

[0034] In the aqueous phase solution, the mass concentration of the anionic surfactant is 0.01-0.1wt%; in the aqueous phase solution, the mass concentration of the cationic surfactant is 0.05-0.5wt%. The mass ratio of the anionic and cationic surfactants is 1-5:10. Preferably, the anionic surfactant is sodium laurate, and the cationic surfactant is hexadecyltrimethylammonium bromide; and in the aqueous phase solution, the mass ratio of the anionic and cationic surfactants is 1-5:10.

[0035] The mixed system of anionic and cationic surfactants can achieve the gelation of n-butanol, and the rheological properties and microscopic morphology of the gel were studied by rheometer, scanning electron microscope, etc. The experiment found that the concentration and mixing ratio of anionic and cationic surfactants have a great influence on the formation of n-butanol gel. The concentration and mixing ratio of anionic and cationic surfactants should be maintained within the above-mentioned limited range for n-butanol to be effectively gelled. And the rheological experiment shows that the gel has the shear-thinning non-Newtonian fluid characteristics (so the shear and disturbance of the continuously escaping CO2 can maintain the three-dimensional structure of the gel). The microscopic morphology study shows that the formed gel has a typical three-dimensional network structure, and the ribbon fibers with relatively uniform thickness are the structural units of the network. Further studies have shown that the hydrophobic effect of the hydrocarbon chain of anionic and cationic surfactants, the electrostatic attraction between polar head groups, and the hydrogen bonding between anionic and cationic surfactants and n-butanol molecules play an important role in the formation of the gel.

[0036] The following are preferred embodiments of the present invention.

[0037] Example 1

[0038] This embodiment provides a method for preparing a high water flux salt lake lithium extraction positively charged nanofiltration membrane, the steps of which are as follows:

[0039] (1) Preparation of aqueous solution

[0040] The aqueous phase solution contains PEI (molecular weight 70000) with a mass concentration of 0.1%, sodium laurate with a mass concentration of 0.01%, hexadecyltrimethylammonium bromide with a mass concentration of 0.1%, and Na2CO3 with a mass concentration of 1%. The aqueous phase solution is kept at 80°C for standby use.

[0041] (2) Preparation of oil phase solution

[0042] The oil phase solution is an isoparaffin Isopar G solution containing 0.10% TMC (trimethylenecarbonyl chloride), and 0.5% n-butanol is added to the oil phase solution. The oil phase solution is kept at 85° C. for standby use.

[0043] (3) Interfacial polymerization reaction and heat treatment

[0044] First, an aqueous solution is coated on the polysulfone base membrane, and the excess aqueous solution is poured out after standing for 60 seconds, and the membrane is blown dry with cold air; then, an oily solution is coated on the dried membrane, and the excess oily solution is poured out after standing for 30 seconds, and the membrane is allowed to stand in the air for 5 seconds, and then the membrane is directly placed in a 100°C oven for heat treatment for 2 minutes to obtain a positively charged nanofiltration membrane.

[0045] Example 2

[0046] This embodiment provides a method for preparing a lithium-extracting positively charged nanofiltration membrane from a salt lake with a high water flux, which is different from the embodiment 1 mainly in that in step (1), the mass concentration of the anionic surfactant sodium laurate is increased to 0.02%. The other steps and conditions are the same as those in the embodiment 1.

[0047] Example 3

[0048] This embodiment provides a method for preparing a lithium-extracting positively charged nanofiltration membrane from a salt lake with a high water flux, which is different from the embodiment 1 mainly in that in step (1), the mass concentration of the anionic surfactant sodium laurate is increased to 0.05%. The other steps and conditions are the same as those in the embodiment 1.

[0049] Example 4

[0050] This embodiment provides a method for preparing a lithium-extracting positively charged nanofiltration membrane from a salt lake with a high water flux, which is different from the embodiment 1 mainly in that: in step (1), the anionic surfactant is replaced with sodium dodecyl sulfate with a mass concentration of 0.08%; the concentration of the cationic surfactant is increased to 0.32%. The other steps and conditions are the same as those in the embodiment 1.

[0051] Example 5

[0052] This embodiment provides a method for preparing a lithium-extracting positively charged nanofiltration membrane from a salt lake with a high water flux, which is different from the embodiment 1 mainly in that: in step (1), the anionic surfactant is replaced with sodium palmitate with a mass concentration of 0.1%; the concentration of the cationic surfactant is increased to 0.5%. The other steps and conditions are the same as those in the embodiment 1.

[0053] Example 6

[0054] This embodiment provides a method for preparing a high water flux salt lake lithium extraction positively charged nanofiltration membrane, which is different from the embodiment 1 mainly in that: in step (1), the cationic surfactant is replaced with hexadecyltrimethylammonium chloride of equal concentration. The other steps and conditions are the same as those in the embodiment 1.

[0055] Example 7

[0056] This embodiment provides a method for preparing a high water flux salt lake lithium extraction positively charged nanofiltration membrane, which is different from the embodiment 1 mainly in that: in step (1), the cationic surfactant is replaced with an equal concentration of hexadecylpyridinium bromide. The other steps and conditions are the same as those in the embodiment 1.

[0057] Example 8

[0058] This embodiment provides a method for preparing a high water flux salt lake lithium extraction positively charged nanofiltration membrane, which is different from the embodiment 1 mainly in that: in step (1), the anionic surfactant is replaced with sodium dodecyl sulfate of equal concentration. The other steps and conditions are the same as those in the embodiment 1.

[0059] Example 9

[0060] The difference between this embodiment and embodiment 1 is that in step (1), the mass concentration of polyethyleneimine (Mw is 100000) in the aqueous phase solution is adjusted to 0.14%, and the rest of the composition of the aqueous phase solution is the same as that in embodiment 1. The other steps and conditions are the same as those in embodiment 1.

[0061] Example 10

[0062] The difference between this embodiment and embodiment 1 is that in step (1), 1% Na2CO3 in the aqueous solution is adjusted to 1.5% NaHCO3. The other steps and conditions are the same as those in embodiment 1.

[0063] Embodiment 11

[0064] The difference between this embodiment and embodiment 1 is that in step (1), the oil phase solution is adjusted to a 0.20% terephthaloyl chloride isoparaffin L solution. The other steps and conditions are the same as those in embodiment 1.

[0065] Example 12

[0066] The difference between this embodiment and embodiment 1 is that in step (1), the oil phase solution is maintained at 95° C. for standby use. The other steps and conditions are the same as those in embodiment 1.

[0067] Embodiment 13

[0068] The difference between this embodiment and embodiment 1 is that in step (1), the aqueous phase solution is maintained at 70° C. for standby use. The other steps and conditions are the same as those in embodiment 1.

[0069] In order to illustrate the influence of each component in the aqueous phase solution and the oil phase solution on the technical solution of the present invention, the following comparative example was obtained by changing some preparation conditions on the basis of the embodiment.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the cationic surfactant hexadecyltrimethylammonium bromide is removed from the aqueous solution. The other steps and conditions are the same as those in Example 1.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 1 is that the anionic surfactant sodium silicate is removed from the aqueous solution. The other steps and conditions are the same as those in Example 1.

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 1 is that the cationic surfactant hexadecyltrimethylammonium bromide and the anionic surfactant sodium laurosilicate are removed from the aqueous solution. The other steps and conditions are the same as those in Example 1.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that n-butanol in the oil phase solution is removed. Other steps and conditions are the same as those in Example 1.

[0078] The positively charged nanofiltration membranes prepared in the above Examples 1-13 and Comparative Examples 1-4 were tested for salt separation efficiency and water flux. The test conditions were as follows: the test pressure was 0.5 MPa, the concentrate flow rate was 1.0 GPM, the ambient temperature was 25°C, and the concentrate pH value was 6.5-7.5. The concentrate was a 2000 ppm LiCl aqueous solution, and the nanofiltration membrane was tested for Li + The lowest retention rate and the highest water flux of the nanofiltration membrane were tested by using a 2000ppm MgCl2 aqueous solution as the concentrate. 2+ Under the test conditions of 1.5MPa, for 200ppm Li +With 10000ppm Mg 2+ Mixed solution (Mg 2+ / Li + The nanofiltration membrane was tested for the highest retention rate of magnesium ions and the lowest retention rate of lithium ions (50:1). The test results are as follows:

[0079]

[0080] As shown in the table above, the positively charged membrane in the embodiment has a positive charge on Li + The lowest retention rate is 17%, and the highest water flux is 99LMH. 2+ The highest interception rate is 98.2%, and the highest water flux is 89LMH. Under the test condition of 1.5MPa, the interception rate of magnesium ions in a mixed solution of 200ppm lithium ions and 1000ppm magnesium ions is 96.7-98.4%, and the interception rate of lithium ions is 3.5-4.5%, which basically realizes the separation of magnesium and lithium.

[0081] Comparing Examples 1-13 with Comparative Examples 1-4, it can be seen that when only cationic surfactants or only anionic surfactants are present in the aqueous phase solution, the water flux of the nanofiltration membrane decreases significantly, and the technical effect of the embodiments of the present invention cannot be obtained. When n-butanol is not added to the oil phase solution, the water flux decreases significantly, and the technical effect of the embodiments of the present invention cannot be obtained.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a lithium-charged positive film from a salt lake, characterized in that: include: S1. Prepare aqueous phase solution and oil phase solution separately The aqueous phase solution contains polyethyleneimine, anionic surfactant, cationic surfactant and carbonate, and the prepared aqueous phase solution is maintained at 65-85° C.; the oil phase solution contains polyacyl chloride monomer and n-butanol, and the prepared oil phase solution is maintained at 75-95° C.; S2. Interfacial polymerization reaction and heat treatment The surface of the base membrane is dipped in an aqueous solution or the aqueous solution is coated on the base membrane, and the aqueous solution is allowed to stand to allow the aqueous solution to adsorb on the base membrane, and the residual aqueous solution on the surface of the base membrane is removed, and the membrane is dried in the shade or blown to obtain a dry membrane sheet; then an oily solution is coated on the dry membrane sheet, and after standing, the residual oily solution on the surface of the membrane sheet is removed, and the membrane sheet is transferred to an oven for heat treatment to obtain a high-throughput salt lake lithium extraction positively charged nanofiltration membrane.

2. The preparation method according to claim 1, characterized in that: In S1, the anionic surfactant is one or more of sodium laurate, sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium palmitate, sodium α-olefin sulfonate, sodium N-oleoyl polypeptide, sodium hexadecyl sulfate, sodium hexadecyl sulfonate and sodium camphor sulfonate; The cationic surfactant is one or more of cetyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, alkylhydroxyethyldimethylammonium chloride, cetylpyridinium bromide, dodecyltrimethylammonium chloride, cetyltrimethylammonium chloride and octadecyltrimethylammonium chloride.

3. The preparation method according to claim 2, characterized in that: In S1, in the aqueous phase solution, the mass concentration of the anionic surfactant is 0.01-0.1 wt %; in the aqueous phase solution, the mass concentration of the cationic surfactant is 0.05-0.5 wt %.

4. The preparation method according to claim 3, characterized in that: In S1, the anionic surfactant is sodium laurate, and the cationic surfactant is cetyltrimethylammonium bromide; in the aqueous phase solution, the mass ratio of the anionic and cationic surfactants is 1-5:

10.

5. The preparation method according to claim 1, characterized in that: In S1, the weight average molecular weight of PEI in the aqueous solution is 1000-150000, and the mass concentration of PEI in the aqueous solution is 0.05-3%.

6. The preparation method according to claim 1, characterized in that: In S1, the carbonate is any one of sodium carbonate, sodium bicarbonate, ammonium carbonate, and ammonium bicarbonate, or a combination of several of them.

7. The preparation method according to claim 1, characterized in that: In S1, the mass concentration of n-butanol in the oil phase solution is 0.1-1%.

8. The preparation method according to claim 1, characterized in that: In S1, the polyacyl chloride monomers in the oil phase solution are one or more of trimesoyl chloride, isophthaloyl chloride, 3,3',5,5'-biphenyltetracarboxylic acid chloride, terephthaloyl chloride, and adipoyl chloride; the solvent of the oil phase solution is one or more of n-hexane, isoparaffin Isopar G, and isoparaffin Isopar L, and the mass concentration thereof is 0.01-2%.

9. The preparation method according to claim 1, characterized in that: In S2, the aqueous solution is first coated on the bottom membrane sheet, and the excess aqueous solution on the bottom membrane surface is removed after standing for 30-70 seconds, and the membrane sheet is blown or dried in the shade, and then the oil solution is coated, and the excess oil solution on the membrane sheet is removed after standing for 30-70 seconds, and the membrane sheet is allowed to stand in the air for 3-10 seconds, and then transferred to a 40-140°C forced air drying oven for treatment for 2-6 minutes to obtain a high-throughput salt lake lithium extraction positively charged nanofiltration membrane.

10. A high water flux salt lake lithium extraction positively charged nanofiltration membrane, characterized in that: The preparation method is described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Novel polyether copolyamide gel membrane and preparation method thereof

    CN103599712A

  • High-throughput positively-charged acid-resistant nanofiltration membrane as well as preparation method and application thereof

    CN109999666A